The comparison study of 5 Fluorouracil vs. cryotherpy in the treatment of the backhand resistant common wart - Rahim Asghariazar; Hamideh Herizchi Ghadim; Shahla Babaeinezhad; Sina Nobahari (Our Dermatology Online, 2014)
Introduction: Wart is a common disease which is caused by a group of viruses called Human Papilloma Virus. The most prevalent type of wart is common wart and the most prevalent site of involvement is hands. Complete recovery, no recurrency and effectiveness in all patients are not obtained by any of therapeutic methods, so in this study we decided to compare therapeutic effects of 5 Fluorouracil (FU) with cryotherapy in treatment of common warts of backhand. Material and Methods: In this study, in a one year period from March 2012 to March 2013, 60 patients that referred to dermatology clinic of Sina hospital included the study with the diagnosis of backhand wart .Patients were divided into two groups of treatment, one treated with cryotherapy (30 patients) and one threated with 5 FU (30 patients). Age and gender of patients, number of lesions and duration of involvement were documented. Treatment by topical 5 FU was implemented for 4 weeks, twice a day for 4 hours each course. Second group was treated by cryotherapy (liquid nitrogen spray, two sessions with a two-week interval between sessions). Their response to treatment was evaluated as good, moderate and weak. Results: There was no difference in age, gender and mean of duration of involvement and number of lesions between two groups. Response to treatment was considerably better in 5 FU group (p=0.02). Also rate of relapse and complications were lower in 5 FU group of treatment, with a statistically significant difference compared to the cryotherapy group (P<0.001). In separate evaluation of complications only scar formation was equal in two groups and pain and bullae formation were lower in 5 FU group with a statistically significant difference (P<0.001 both). Conclusions: According to limited studies in this field, results of this study could be the base of more comprehensive studies in evaluating the efficacy of 5 FU in treatment of common warts. Appropriate therapeutic response in addition to lower rates of relapse and complications by 5 FU treatments can make a major change and lower the psychosocial burden of this disease dramatically.